PATHOPHYSIOLOGY AND MANAGEMENT OF CEREBRAL EDEMA - Husna, Ully; Dalhar, Mochamad (Malang Neurology Journal, 2017)
Cerebral edema comprehensively defined as a pathological increase of water in the whole brain that leads to an increased of brain volume. Cerebral edema can be classified into focal or global topography. According to the etiology, it can be categorized as cytotoxic, vasogenic, interstitial, or a combination. The symptoms of cerebral edema are not specific and are associated with secondary effects of mass, vascular compression and herniation. Clinical and radiological changes are usually reversible in the early stages during the underlying cause is corrected. Cerebral edema need to be discussed more specifically in the pathophysiology and management. By understanding the pathophysiology and management quickly and accurately will be able to improve the prognosis of patients with cerebral edema.